Does Fisher Hypothesis Hold for the East Asian Economies? An Application of Panel Unit Root Tests - Tai-Hu, Ling; Venus, Khim-Sen Liew; Syed Azizi Wafa, Syed Khalid Wafa (Palgrave Macmillan publishes, 2010)
This study provides evidence supportive of Fisher hypothesis in East Asian economies using panel unit root tests, which allow for the consideration of crosscountry interdependence of real interest rates in the estimation. One important implication of our finding is that monetary policy will be more effective in influencing long-term interest rates and long-run macroeconomic stability in these East Asian economies with regional collaboration.